Principles of assessment in school-based making. (2nd January 2023) - Murai, Yumiko; Kim, Yoon Jeon; Chang, Stephanie; Reich, Justin
ABSTRACT: While school educators are increasingly interested in adopting maker pedagogy, many schools struggle to integrate making with their existing core curriculum because of the difficulty in assessing the learning that occurs in maker classrooms. To address this issue, we collaborated with educators on design-based research focused on assessment in maker classrooms. We investigated assessment approaches that support the process of making. This paper reports on four design principles of assessment in school-based making that emerged from a literature review and the collaborative development process with educators. We discuss the challenges and opportunities for assessment in maker classrooms, as well as strategies to seamlessly embed assessment within a classroom's culture, norms, and activities.